How genomic and environmental relationships shape phenotypic plasticity in brook charr Salvelinus fontinalis: an historical review - Audet, Céline; Garant, Dany; Crespel, Amélie; Vagner, Marie (Frontiers in Fish Science, 2025)
This review revisits 20 years of collaborative studies that were pursued with Louis Bernatchez who sadly passed away in October 2023. With him, we explored the phenotypic plasticity of brook charr by combining ecophysiology, genetics, genomics, and more recently epigenetics. Over the years, we conducted extensive studies on brook charr, focusing on metabolism, stress response, growth regulation, and temperature tolerance across various strains. Our research highlighted the remarkable diversity in physiological responses to temperature and salinity conditions, along with significant differences in the heritability of key traits across different strains and life stages. We studied stages from yolk-sac fry to reproductive adults, compared freshwater residents and anadromous fish, and recently showed how epigenetics affects the physiological and transcriptomic responses of progeny to temperature conditions. This review highlights the incredible physiological plasticity of brook charr and presents future research avenues that will lead to a better understanding of how the species may face challenges related to global changes.